THD Reduction of Improved Single Source MLI Using Upgraded Black Widow Optimization Algorithm - Rupali Mohanty; Debashis Chatterjee; Satyajit Mohanty; C. Dhanamjayulu; Baseem Khan (International Transactions on Electrical Energy Systems)
An upgraded Black Widow Optimization algorithm for obtaining the ideal switching angles of a reduced structure multilevel inverter is proposed in this paper with minimum voltage THD. The conventional BWO algorithm has been modified and proposed to solve the THD minimization problem with faster convergence rate, lesser tuning variables, and lesser number of equations than the other existing nature inspired algorithms. The reduced structure MLI is designed with three asymmetrical DC voltage sources of ratio 1 : 2 : 4 to generate 15-level output voltage which requires reduced number of switching devices in comparison with the existing topologies of equivalent voltage level. The asymmetrical DC voltage sources to the MLI are derived from a single DC voltage source using a multisecondary winding DC-DC converter in order to provide the isolation between the load side and source side. The proposed modified BWO algorithm reduces the complexity of solving the nonlinear equations to achieve the best result by avoiding the local optima. To verify the effectiveness of the upgraded BWO algorithm, the optimization problem for three phase fifteen level MLI has been solved using the genetic algorithm, BFO algorithm, and PSO algorithm. The results for the above three applied algorithms are compared with the upgraded BWO and presented. The proposed algorithm has minimized the output voltage THD to 1.83% at 0.88 modulation index. The developed scheme has been corroborated with the help of MATLAB simulation and the results have been verified through a hardware model developed in laboratory.